Digital Learning Library Reconstruction for Early Childhood Education - Dian Cita Sari; Widdya Rahmalina (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2023)
The reconstruction of the digital learning space for ealy childhood education an important role in learning the Indonesian. One of them in childhood literacy learning. Aside from being a source of learning for the learning community, childhood literacy is also the basis for childhood competing in the revolutionary 4.0 era, ranging from infrastructure development, expansion and learning performance which will become an asset of Indonesia. Simultaneous collaboration efforts with multi-effect players are needed to improve the public literacy index. One of the efforts is through the Reconstruction of digital library learning for early childhood education. The analysis technique in this research is the content analysis.